The Role of the Family Assistance Team (TPK) in Preventing Stunting in Todller in the Community - Gusti Ayu Ketut Putri Widnyani; Ni Putu Wiwik Oktaviani; I Made Sudarma Adiputra; Ni Wayan Trisnadewi (GLOBAL HEALTH SCIENCE GROUP, 2023)
Indonesia is still facing nutritional problems that have a serious impact on the quality of human resources and can cause short toddlers or stunting. The Indonesian government is trying to reduce the stunting rate by developing a strategy to involve health workers in a family approach program that assists families at risk of stunting, known as the Family Assistance Team. This study aims to describe the role of the Family Assistance Team in preventing stunting in toddlers in the working area of ​​Puskesmas II Blahbatuh, Gianyar Regency, Bali Province. This study used a descriptive research design using a purposive sampling technique, and data collection was carried out by distributing questionnaires to 62 respondents. Data was analysis with descriptive analysis. The results of the study showed that 62 respondents (100%) were optimally carrying out the role of the Family Assistance Team, as seen by all respondents getting a score ≥ 44. Respondents carried out stunting prevention activities targeting prospective brides, pregnant women, postpartum mothers, and children aged 0-59 months, namely by conducting screening, mentoring, and counseling.